Chimeric Tobamoviruses With Coat Protein Exchanges Modulate Symptom Expression and Defence Responses in Nicotiana tabacum - Man Yu; Xinyue Bi; Yuanmin Huang; Yong Chen; Jun Wang; Ruina Zhang; Yunkang Lei; Zihao Xia; Mengnan An; Yuanhua Wu (Frontiers in Microbiology, 2020)
In the pathogen infection and host defence equilibrium, plant viruses have evolved to efficiently replicate their genomes, to resist the attack from host defence responses and to avoid causing severe negative effect on growth and metabolism of the hosts. In this study, we generated chimeric tobacco mosaic virus (TMV) variants, in which the coat protein (CP) sequences were substituted with that of cucumber green mottle mosaic virus (CGMMV) or pepper mild mottle virus (PMMoV) to address the role of these in virus infection and host symptomology. The results showed that the chimeric viruses (TMV-CGCP or TMV-PMCP) induce stunting and necrotic symptoms in tobacco plants. We analyzed the transcriptomic changes in tobacco plants after infection of TMV and its chimeras using a high-throughput RNA sequencing approach and found that infection of the chimeric TMV induced significant up-regulation of host defence responsive genes together with salicylic (SA) or abscisic acid (ABA) responsive genes, but down-regulation of auxin (Aux) responsive genes. We further confirmed the increase in the levels of SA and ABA, together with the reduced levels of Aux after infection of chimeric TMV in tobacco plants. These data suggest novel roles of tobamovirus CP in induction of host symptoms and defence responses.